History of Development of Family Business in Uzbekistan and Its Regions - Doston Ashurov (International Journal of Formal Education, 2024)
The article highlights the policy of the government of Uzbekistan aimed at the development of family business and its practical implementation in the Bukhara and Navoi regions. Implementation of programs for the revival of folk crafts, tourism activities, dean's economy, home-based work, as well as solving the problems of employment of the population, especially in remote villages and regions.